DETERMINAN PENGUNGKAPAN MODAL INTELEKTUAL PADA PERUSAHAAN PERBANKAN - Delima, Zamrud Mirah; Zuliyati, Zuliyati (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2020)
The purposed of this research is to analyze the factors which influence of intellectual capital disclosure. Knowledge of intellectual capital disclosure in the digital era was the important contributing factor to increase performance, professionalism, and sustainable of value excellence for banking companies in Indonesia for performance more optimally. The factors that tested in this research were leverage, earning growth, company size, board of commissioner size, company age, and business complexity toward intellectual capital disclosure. The method of data collecting in this research was taken banking companies which registered at Indonesia Stock Exchange in period 2013 until 2019 as the object. The sampling that used in this research was purposive sampling technique and gained the data of 175 companies which registered at Indonesia Stock Exchange in period 2013 until 2019. The method of analyze that used was multiple regression analysis. The result of the hypothesis testing in this research showed that leverage, company size, board of commissioner size, business complexity had significant influence, where as earning growth and company age were not effect toward intellectual capital disclosure.